THE IMPACT OF AUDIT RATE, PERCEIVED PROBABILITY OF AUDIT ON TAX COMPLIANCE DECISION: A Laboratory Experiment Study) - Meinarni Asnawi (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
This study aims to provide empirical evidence that audit rate and perceived probability of audit have impact on tax compliance. This study used a laboratory experiment to test the impact of economic factor (audit rate) and psychology factor (perceived probability of audit) on tax compliance decision. 78 participants were involved in this experiment from the master of science and doctoral program and accounting magister of FEB UGM Yogyakarta. This experiment used multilevel treatment experiment design and standard of fieldwork media for software. The results provide empirical evidence that audit rate and perceived probability of audit have significant relationship with tax compliance decision. Audit rate has indirectly related to tax compliance decisions by perceived probability of audit. We propose a model that is intended to clarify the mechanism through perceived probability of audit impact to tax compliance decisions. The result highlights the importance of obtaining a proper understanding of these factors for developing effective policies with the aim of increasing the level of compliance, and indicate that audit rate should be implemented to improve tax accuration report using perceived robability of audit by tax payer.